Pendanaan Lembaga Penyelenggara Pemilu (EMB) - Qori Mughni Kumara (Universitas Airlangga, 2022)
This article reveals that the financial funding of the election management body (KPU) to support the stages of general election management still relies on the state budget. This condition happens considering that elections are a five-year periodic agenda in accordance with the foundation of the constitution. There are three models of election financing, namely core cost or direct financing; diffuse cost or indirect financing; and integrity costs or financing to develop the integrity of organizers so that elections run democratically. This research used the literature method, combined with the results of direct observation, and it found that the dependence of election financing on the state makes the KPU inflexible in drafting election financing activities because it must consult with the government as the owner of the budget and the DPR as political stakeholders.